Níveis de vitamina “e” em dietas de frangos sobre o desempenho, características da carcaça e da carne e resposta imune - Alexandre, Natani Cruz [UNESP] (2014)
This study aimed to evaluate the effects of vitamin E levels in broiler diets on performance, carcass characteristics, meat quality and immune system of birds. 1050 chicks of Cobb strain were distributed in a completely randomized design with five treatments and six replicates of 35 birds per experimental plot. The experimental diets were formulated based on corn and soybean meal according to the dietary recommendations for broilers to Brazilian Tables for Poultry and Swine and divided into four phases: pre-starter ( 1-7 days) , early ( 8-21 days) , growth ( 22-35 days) and late ( 36-42 days old ) and that the basal diet met the requirements of vitamin E proposed to the aforementioned phases ( 35 , 31 , 28, 21 IU / kg diet, respectively). For performance variables were not obtained difference between treatments, as well as parts and carcass yield and meat quality analysis, however, for thiobarbituric acid reactive substances (TBARS) for breast and drumstick species difference was obtained at 30 and 60 days of storage, as well as in plasma oxidation. In the analysis of titers of antibodies against the virus of Gumboro disease to vitamin E resulted in no difference in the immune response of the birds. It can be concluded that the administration of high doses of vitamin E does not directly affect production indices, carcass yield and cuts, as well as the parameters of meat quality and immune activity. Inclusion levels of 52.5; 46.5; 56 and 63 IU vitamin E / kg of diet on 1-7; 8-21; 22-35 and 36-42 days of age reduce oxidation of the tissues and blood plasma, demonstrating the antioxidant properties of vitamin E